Studies on the red sea sponge Haliclona sp. for its chemical and cytotoxic properties - Al-Massarani, Shaza Mohamed; Ali El-Gamal, Ali; Al-Said, Mansour Sulaiman; Abdel-Kader, Maged S; Ashour, Abdelkader Elbadawy Abbas; Kumar, Ashok; Abdel Mageed, Wael M; Al Rehaily, Adnan Jathlan; Ghabbour, Hazem A.; Fun, Hoong-Kun (Wolters Kluwer - Medknow, 2016)
BACKGROUND: A great number of novel compounds with rich chemical diversity and significant bioactivity have been reported from Red Sea sponges.